Aggressive recurrent urachal adenocarcinoma: A case report and review of the literature - Zainal Adwin Zainal Abidin; Mohamed Arif Hameed Sultan; Firdaus Hayati; Zulkifli Zainuddin (Ibn Sina Trust, 2021)
Recurrent urachal adenocarcinomas are rare. It is commonly associated with poor prognosis. A 51-year-old woman underwent a partial cystectomy for urachal cancer in 2014. She was well throughout follow-up with annual cystoscopies. She presented with a 1-month history of rapidly progressive suprapubic mass and hematuria. A contrasted computed tomography scan of the thorax, abdomen and pelvis showed a large mixed solid cystic tumour at the right lumbar region, suprapubic area and also at the pouch of Douglas. She refused surgical extirpation and now on chemotherapy. Urachal adenocarcinoma is rare, and resection is commonly advocated; usually, no standard adjuvant therapy is advocated. Recurrent cancers represent a management dilemma, and no standard follow-up protocols exist.